2013
DOI: 10.1159/000345498
|View full text |Cite
|
Sign up to set email alerts
|

Hemithyroidectomy: A Meta-Analysis of Postoperative Need for Hormone Replacement and Complications

Abstract: Background: We sought to determine certain factors predicting postoperative need for hormone replacement therapy (HRT) after hemithyroidectomy. Methods: A PubMed search was conducted to identify articles with separate cohorts for total and hemithyroidectomy. Outcomes of interest included hypothyroidism and complications. Results: Of 50,445 patients, 15,412 (30.6%) underwent hemithyroidectomy. The reported incidence rate of postoperative hypothyroidism was 10.9-48.8%. The pooled mean preoperative thyroid-stimul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
77
1
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(86 citation statements)
references
References 80 publications
(67 reference statements)
2
77
1
4
Order By: Relevance
“…A higher TSH preoperatively in patients undergoing a hemithyroidectomy indicates a lower thyroid function reserve and tend to develop hypothyroidism. A recent meta‐analysis showed that patients with a preoperative TSH above 2.5 μIU/L are three times (RR: 3.16) more likely to develop hypothyroidism postoperatively . In our study preoperative TSH above 2.5 significantly did not predict for postoperative hypothyroidism, unlike other studies.…”
Section: Discussionsupporting
confidence: 86%
“…A higher TSH preoperatively in patients undergoing a hemithyroidectomy indicates a lower thyroid function reserve and tend to develop hypothyroidism. A recent meta‐analysis showed that patients with a preoperative TSH above 2.5 μIU/L are three times (RR: 3.16) more likely to develop hypothyroidism postoperatively . In our study preoperative TSH above 2.5 significantly did not predict for postoperative hypothyroidism, unlike other studies.…”
Section: Discussionsupporting
confidence: 86%
“…We found no significant difference in the rate of permanent complications when we compared those with pre- versus postoperatively diagnosed PTMC; however, the study was significantly underpowered to detect a difference in outcomes. Larger studies of patients undergoing thyroid surgery demonstrate appreciably higher risks of permanent complications for TT compared to TL (10, 35). While these rates tend to be low, the risk of complications is higher in low-volume surgeons who perform the majority of thyroid surgery in the United States.…”
Section: Discussionmentioning
confidence: 99%
“…First, lobectomy is inherently associated with lower operative risks than TT, particularly related to postoperative hypoparathyroidism, although both operations are quite safe, particularly in high-volume surgeon/center settings. Although extremely rare, the devastating risk of bilateral recurrent laryngeal nerve injury requiring tracheostomy is avoided with lobectomy (9). Having a remaining lobe may also obviate the need for thyroid hormone replacement in more than half of patients when thyrotropin suppression may not be necessary (10).…”
Section: Discussionmentioning
confidence: 99%